W jaki sposób mówimy dzieciom o wojnie? Charakterystyka prozy o tematyce wojennej na podstawie wybranych książek dla dzieci - Sikora, Aleksandra (Acta Universitatis Lodziensis. Folia Librorum, 2014)
The subject of this article is war–themed prose addressed to children, or more precisely, the examination of a series of books published under the auspices of the Warsaw Uprising Museum as well as two short stories by Batszewa Dagan published by the Memorial and Museum Auschwitz–Birkenau in Auschwitz. The objective of the article is the comparison of methods of presenting the subject of war to a young reader; specific issues disscussed in this article include narration, language, educational value and use of illustrations.